Follicle –Stimulating Hormone Receptor Polymorphisms in Iraqi Women with Primary Amenorrhea - Rawan Ahmed Nijeeb1, Abdul Kareem A.Alkazaz1, Ruqayah Gheyath Yaseen2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study was carried to determine Single Nucleotide Polymorphism (rs6165) of Follicle Stimulating Hormone Receptor (FSHR) gene in blood samples of 62 Iraqi women with primary amenorrhea and 40 healthy control females. The research included chromosomal study and serum analysis of 62 patient samples. The samples were collected from Educational laboratories, City of Medicine, Baghdad and Biotechnology Dept. College of Science- Baghdad University through the period from October 2018 to March 2019. The determinations of SNP (rs6165) were carried out by real-time PCR. Results of rs6165 genotyping showed significant variations between PA patients and controls, Inspecting FSHR gene genotypes and allele frequencies in PA patients groups with the control group, revealed that there was significant variation in the heterozygous (AG) and homozygous mutant type(AA) genotype frequencies in (rs6165). the SNP of target gene may have a role in PA patients complaining from idiopathic puberty problems.